Investigation on the planning and development of selected neighbouring cities - Rabe, Noor Suzilawati; Mohamed Osman, Mariana; Abdullah, Muhammad Faris; Abdul Halim, Izzatul A'syiqin (2020)
The deficiency of policy and planning guideline regulation administering the neighbouring cities process has resulted in crucial urbanisation issues in the planning and development. This study analysed the neighbouring city's perception of the investigation of the neighbouring cities by examining planning’s local authority, planning developer, and planning consultant’s knowledge about neighbouring cities. In 50 questionnaire survey distributed to local authority department, planning developer, and consultant agencies in selected neighbouring cities in Malaysia, Cronbach’s alpha and reliability analysis were applied for the method in this paper. The result shows that 80% of the respondent know what neighbouring cities are and can explain the planning process of neighbouring cities. These results have recommended strategies to introduce the proper policy and guidelines for the neighbouring cities